Research outside academia? – An analysis of resources in extra‐academic report writing. Issue 1 (27th December 2016) - Börjesson, Lisa
ABSTRACT: A significant part of all research takes place in extra‐academic organizations. Practitioner researchers often present their results in publications different from those in academia, e.g. in reports, sometimes (and here) referred to as "gray literature". Gray literature is increasingly available online. However, availability does not mean that reports are exploited to their full potential in research. Disciplines like archaeology have substantial problems with the scholarly communication and knowledge sharing between extra‐academic and academic research. This paper approaches this problem from a report‐user perspective. For the benefit of potential report users' gray literature literacies, report‐writing practices are analyzed by means of practice theory. Qualitative interviews with six practitioner researchers in Swedish archaeology firms make up the material. The analysis focuses on how report writers draw on regulative, institutional, and infrastructural resources in their practices. Based on the findings about the practices in which reports are written and become informative, the paper presents seven suggestions supporting report users' potential to critically analyze and use report content. The results contribute to the information science field with insights into extra‐academic information practices, and as input in a wider critical discussion of the information‐related conditions for research outside academia.